A dry powder polymer online mixing fracturing method for oil and gas fields

The thickening agent was prepared by using polyethyleneimine and 6-[(4-azido-2-nitrophenyl)amino]hexanoic acid sulfonate succinimide ester to form a high-efficiency crosslinking network, solving the traditional pressure The problem of degradation of cracking fluid in high-temperature and high-pressure environments has significantly improved the stability and applicability of the fracturing fluid.

CN119145828BActive Publication Date: 2025-02-11山东德坤工贸有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411614853.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-02-11
Estimated Expiration
2044-11-13

AI Technical Summary

Technical Problem

Traditional fracturing fluid is prone to degradation or decreases in high temperature and high pressure environments, resulting in a decrease in the performance of fracturing fluid and affecting the fracturing effect.

Method used

The thickening agent is prepared by polyethyleneimine and 6-[(4-azido-2-nitrophenyl)amino]hexanoic acid sulfonate succinimide ester, and N-hydroxysuccinimide (NHS) Ester and photoactivated nitrophenyl azide are crosslinked with polyethyleneimine to form an efficient crosslinking network to improve the stability and viscosity of the fracturing fluid.

Benefits of technology

It significantly improves the stability and reaction efficiency of the fracturing fluid, enhances the sand carrying capacity and suspension ability, ensures the structural integrity of the fracturing fluid in a high-temperature and high-pressure environment, and broadens its applicability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention relates to the technical field of dry powder polymers, and in particular to an online mixing and fracturing method for dry powder polymers for oil and gas fields. S1.1, weighing the following raw materials in parts by weight: 1-10 parts by weight of a thickener, 18-23 parts by weight of hydroxypropyl guar gum, 11-15 parts by weight of polyacrylamide, 2-6 parts by weight of borax, 1-3 parts by weight of zirconate, 3-6 parts by weight of a sodium hydroxide pH value regulator, 0.1-0.5 parts by weight of a diethylenetriamine pentaacetic acid antiscalant, and 0.5-0.7 parts by weight of sodium lauryl sulfate; The thickener is prepared by mixing polyethyleneimine and 6-[(4-azido-2-nitrophenyl)amino]hexanoic acid sulfonic acid succinimide ester in a mass ratio of 1:0.05-0.1; S1.2, adding raw materials into a dry material system and mixing them evenly; S1.3, adding water and mixing in a high-speed agitator to prepare a fracturing fluid; the thickener is used to increase the viscosity of the polymer through a double cross-linking mechanism, enhance the stability of the fracturing fluid, improve the sand carrying capacity and suspension capacity of the fracturing fluid, and broaden the applicability of the fracturing fluid.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of dry powder polymers, in particular to an online mixing and fracturing method for dry powder polymers used in oil and gas fields. Background Art

[0002] The dry powder polymer online mixing fracturing method is an advanced oil and gas field exploitation technology. Its core lies in the on-site instant mixing of dry powder polymer fracturing fluid. The traditional mixing method, such as centralized mixing in a fixed mixing station, has problems such as backward technology, slow mixing speed, high transportation cost, and uneven dispersion of fracturing fluid. These have affected the effect of fracturing and seam creation to a certain extent. In order to solve these problems, the dry powder online mixing technology came into being. This method uses a special dispersion and mixing device to mix dry powder polymer, water and other necessary additives on site. It can not only adjust the viscosity of the fracturing fluid in real time according to on-site needs, but also achieve full transformation of the fracture network at all levels of the formation. More importantly, it solves a series of problems such as advance mixing, transportation, storage and residual liquid treatment of fracturing fluid in large-scale construction. It has multiple advantages such as cost saving, safety and environmental protection, and reduced reservoir damage. The dry powder polymer online mixing fracturing method plays an increasingly important role in oil and gas field development with its advantages of high efficiency, environmental protection and flexibility.

[0003] Traditional fracturing fluids often degrade or lose activity under high temperature and high pressure, which leads to a decrease in the performance of the fracturing fluid and affects the fracturing effect. In view of this, we propose an online fracturing method for dry powder polymers for oil and gas fields. Summary of the invention

[0004] The object of the present invention is to provide an online mixing and fracturing method of dry powder polymer for oil and gas fields to solve the problems raised in the above background technology.

[0005] To achieve the above object, the present invention provides an online mixing and fracturing method for dry powder polymer for oil and gas fields, S1.1, weigh the following raw materials in parts by weight: 1-10 parts by weight of thickener, 18-23 parts by weight of hydroxypropyl guar gum, 11-15 parts by weight of polyacrylamide, 2-6 parts by weight of borax, 1-3 parts by weight of zirconate, 3-6 parts by weight of sodium hydroxide pH regulator, 0.1-0.5 parts by weight of diethylenetriaminepentaacetic acid antiscalant and 0.5-0.7 parts by weight of sodium dodecyl sulfate;

[0006] The thickener is prepared by mixing polyethyleneimine and 6-[(4-azido-2-nitrophenyl)amino]hexanoic acid sulfonic acid succinimide ester in a mass ratio of 1:0.05-0.1;

[0007] S1.2. Add thickener, hydroxypropyl guar gum, polyacrylamide, borax, zirconate, sodium hydroxide pH regulator, diethylenetriamine pentaacetic acid antiscalant and sodium lauryl sulfate powder to the dry powder feeding system in sequence, and stir with a stirrer to mix the raw materials evenly;

[0008] S1.3. Use a high-speed agitator with an efficient dispersion system to add water into the mixing tank, and add the dry powder into the water through the dry powder feeding system at a stirring rate of 600-1000rpm until the polymer is completely dissolved to form a uniform solution to obtain the fracturing fluid.

[0009] Preferably, in S1.3, the addition rate of the dry powder feeding system is 0.5-1% of the total mass of dry powder added per minute.

[0010] The total mass of dry powder refers to the sum of the masses of thickener, hydroxypropyl guar gum, polyacrylamide, borax, zirconate, sodium hydroxide pH adjuster, diethylenetriamine pentaacetic acid antiscalant and sodium dodecyl sulfate.

[0011] Preferably, the steps of preparing the thickener are specifically as follows:

[0012] Use a metering pump to add polyethyleneimine to water at 25-35°C, turn on a high shear mixer to stir thoroughly until it is completely dissolved, then add oleic acid, continue stirring until it is completely evenly distributed, then add 6-[(4-azido-2-nitrophenyl)amino]hexanoic acid sulfonic acid succinimide ester to the solution containing polyethyleneimine and oleic acid, adjust the pH of the mixed solution to 7-8 with a sodium hydroxide solution, stir the reaction for 30-40 minutes under light-proof conditions, turn on a UV light source to irradiate the mixed solution, and continue stirring for 10-20 minutes. After the irradiation is completed, add glycine to terminate the remaining active sites, use a centrifuge to separate and purify, wash with deionized water, and then place in a freeze dryer, set the temperature to minus 30-50°C and the vacuum degree to 0.1-0.3mbar for sublimation drying, and the drying time is 12-48h to obtain a thickener.

[0013] Polyethyleneimine (PEI) is a water-soluble polymer. The PEI molecular chain contains a large number of primary amine, secondary amine and tertiary amine groups, which give it excellent coordination ability; 6-[(4-azido-2-nitrophenyl)amino] hexanoic acid sulfonic acid succinimide ester (Sulfo-SANPAH) is a unique heterobifunctional cross-linking agent. Sulfo-SANPAH has excellent water solubility and can be quickly dissolved without the use of organic solvents, which provides convenience for online mixed fracturing. It has two functional groups, amine-reactive N-hydroxysuccinimide (NHS) ester and photoactivated nitrophenyl azide. Its photosensitive group will react under ultraviolet irradiation to generate highly reactive nitrene groups, which further participate in cross-linking reactions; NHS ester groups show good reactivity under mild conditions and can undergo acylation reactions with active hydrogen-containing functional groups (such as primary amine groups). This feature makes Sulfo-SANPAH It can effectively identify and bind to the amino group on the PEI molecular chain. The specific reaction principle is: the primary amine group on the PEI molecular chain quickly identifies the succinimide ester group in the Sulfo-SANPAH molecule. The primary amine group, relying on its nucleophilicity, actively attacks the exposed electrophilic carbon atom in the succinimide ester group. As the reaction proceeds, a new amide bond is eventually formed, tightly connecting PEI and Sulfo-SANPAH together. In addition, the nitrophenyl azide in Sulfo-SANPAH will trigger a photoactivation reaction under ultraviolet irradiation to generate a highly reactive nitrene group. This nitrene group can react with a variety of nucleophilic groups (such as primary amine groups, CH and NH sites) to further form covalent bonds. This reaction mechanism enables Sulfo-SANPAH to achieve double cross-linking. This double cross-linking mechanism greatly improves the viscosity of PEI, thereby enhancing the stability and reaction efficiency of the fracturing fluid.

[0014] Therefore, in the pore structure of the formation rock, this cross-linked network can not only increase the viscosity of the fracturing system, but also act like a "sieve" to prevent the liquid phase components in the fracturing fluid from penetrating too quickly into the deep pores of the rock, so that the fracturing fluid can maintain a higher pressure in the cracks, effectively open the cracks, and improve its utilization efficiency. By further increasing the degree of cross-linking, the high temperature and high pressure resistance of the fracturing fluid is improved, ensuring the stability and effectiveness of the fracturing fluid in complex underground environments, and maintaining its structural integrity even under extreme underground conditions. The cross-linked fracturing fluid also has higher viscosity and better rheology, which helps to improve the sand carrying capacity and suspension capacity of the fracturing fluid. Therefore, compared with the addition of a single polyethyleneimine cross-linking agent, it has better stability and sand carrying capacity, and improves the applicability of the fracturing fluid.

[0015] Preferably, the molecular weight of the polyethyleneimine is 500-750 kDa.

[0016] Preferably, the mass fraction of the polyethyleneimine solution is 1-3%.

[0017] Preferably, the mass fraction of oleic acid is 1-10%.

[0018] Preferably, the mass ratio of oleic acid to polyethyleneimine is 0.001-0.01:1.

[0019] Preferably, the mass fraction of the sodium hydroxide solution is 1-5%.

[0020] Preferably, the wavelength range of the UV-A light source is 320-365 nm.

[0021] Preferably, the molar ratio of glycine to 6-[(4-azido-2-nitrophenyl)amino]hexanoic acid sulfosuccinimide ester is 1.2-1.5:1.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] In the online fracturing method of dry powder polymer for oil and gas fields, polyethyleneimine and 6-[(4-azido-2-nitrophenyl)amino]hexanoic acid sulfonic acid succinimide ester are used to prepare a thickener, and N-hydroxysuccinimide (NHS) ester and photoactivated nitrophenyl azide are cross-linked with the amino group on polyethyleneimine. The viscosity of polyethyleneimine is greatly improved through a double cross-linking mechanism, thereby enhancing the stability and reaction efficiency of the fracturing fluid, helping to improve the sand carrying capacity and suspension capacity of the fracturing fluid, ensuring the structural integrity of the fracturing fluid under high temperature and high pressure environment, and thus broadening the applicability of the fracturing fluid. DETAILED DESCRIPTION

[0024] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0025] The present invention provides an online mixing and fracturing method for dry powder polymers for oil and gas fields:

[0026] S1.1, weigh the following raw materials in parts by weight: 1-10 parts by weight of thickener, 18-23 parts by weight of hydroxypropyl guar gum, 11-15 parts by weight of polyacrylamide, 2-6 parts by weight of borax, 1-3 parts by weight of zirconate, 3-6 parts by weight of sodium hydroxide pH regulator, 0.1-0.5 parts by weight of diethylenetriamine pentaacetic acid antiscalant and 0.5-0.7 parts by weight of sodium lauryl sulfate;

[0027] The thickener is prepared by mixing polyethyleneimine and 6-[(4-azido-2-nitrophenyl)amino]hexanoic acid sulfonic acid succinimide ester in a mass ratio of 1:0.05-0.1;

[0028] S1.2. Add thickener, hydroxypropyl guar gum, polyacrylamide, borax, zirconate, sodium hydroxide pH regulator, diethylenetriamine pentaacetic acid antiscalant and sodium lauryl sulfate powder to the dry powder feeding system in sequence, and stir with a stirrer to mix the raw materials evenly;

[0029] S1.3. Use a high-speed agitator with an efficient dispersion system to add water into the mixing tank, and add the dry powder into the water through the dry powder feeding system at a stirring rate of 600-1000rpm until the polymer is completely dissolved to form a uniform solution to obtain the fracturing fluid.

[0030] Embodiment 1: A method for online fracturing of dry powder polymer for oil and gas fields, comprising the following steps:

[0031] S1.1, weigh the following raw materials in parts by weight: 5 parts by weight of thickener, 23 parts by weight of hydroxypropyl guar gum, 15 parts by weight of polyacrylamide, 6 parts by weight of borax, 3 parts by weight of zirconate, 6 parts by weight of sodium hydroxide pH regulator, 0.5 parts by weight of diethylenetriamine pentaacetic acid antiscalant and 0.7 parts by weight of sodium lauryl sulfate;

[0032] The thickener is prepared by mixing polyethyleneimine and 6-[(4-azido-2-nitrophenyl)amino]hexanoic acid sulfonyl succinimide ester in a mass ratio of 1:0.05; the mass ratio of oleic acid to polyethyleneimine is 0.01:1; the molar ratio of glycine to 6-[(4-azido-2-nitrophenyl)amino]hexanoic acid sulfonyl succinimide ester is 1.5:1;

[0033] Use a metering pump to add polyethyleneimine with a molecular weight of 750 kDa to water at 25°C, the mass fraction of the polyethyleneimine solution is 1%, turn on a high shear mixer to stir thoroughly until it is completely dissolved, then add oleic acid with a mass fraction of 1%, continue stirring until it is completely evenly distributed, then add 6-[(4-azido-2-nitrophenyl)amino]hexanoic acid sulfonic acid succinimide ester to the solution containing polyethyleneimine and oleic acid, adjust the pH of the mixed solution to 8 with a mass fraction of 3% sodium hydroxide solution, stir the reaction for 30 minutes under light-proof conditions, turn on a UV light source with a wavelength of 365 nm to irradiate the mixed solution, continue stirring for 20 minutes, after the irradiation is completed, add glycine to terminate the remaining active sites, use a centrifuge to separate and purify, wash with deionized water, and then place in a freeze dryer, set the temperature to minus 50°C and the vacuum degree to 0.1 mbar for sublimation drying, and the drying time is 48 hours to obtain a thickener;

[0034] S1.2. Add thickener, hydroxypropyl guar gum, polyacrylamide, borax, zirconate, sodium hydroxide pH regulator, diethylenetriamine pentaacetic acid antiscalant and sodium lauryl sulfate powder to the dry powder feeding system in sequence, and stir with a stirrer to mix the raw materials evenly;

[0035] S1.3. Use a high-speed agitator with an efficient dispersion system to add water into the mixing tank, and add dry powder into the water through the dry powder feeding system. The addition rate is 1% of the total mass of dry powder per minute, and the stirring rate is 1000rpm, until the polymer is completely dissolved to form a uniform solution to obtain the fracturing fluid.

[0036] Embodiment 2: A method for online fracturing of dry powder polymer for oil and gas fields, comprising the following steps:

[0037] S1.1, weigh the following raw materials in parts by weight: 5 parts by weight of thickener, 23 parts by weight of hydroxypropyl guar gum, 15 parts by weight of polyacrylamide, 6 parts by weight of borax, 3 parts by weight of zirconate, 6 parts by weight of sodium hydroxide pH regulator, 0.5 parts by weight of diethylenetriamine pentaacetic acid antiscalant and 0.7 parts by weight of sodium lauryl sulfate;

[0038] The thickener is prepared by mixing polyethyleneimine and 6-[(4-azido-2-nitrophenyl)amino]hexanoic acid sulfonyl succinimide ester in a mass ratio of 1:0.08; the mass ratio of oleic acid to polyethyleneimine is 0.01:1; the molar ratio of glycine to 6-[(4-azido-2-nitrophenyl)amino]hexanoic acid sulfonyl succinimide ester is 1.5:1;

[0039] Use a metering pump to add polyethyleneimine with a molecular weight of 750 kDa to water at 25°C, the mass fraction of the polyethyleneimine solution is 1%, turn on a high shear mixer to stir thoroughly until it is completely dissolved, then add oleic acid with a mass fraction of 1%, continue stirring until it is completely evenly distributed, then add 6-[(4-azido-2-nitrophenyl)amino]hexanoic acid sulfonic acid succinimide ester to the solution containing polyethyleneimine and oleic acid, adjust the pH of the mixed solution to 8 with a mass fraction of 3% sodium hydroxide solution, stir the reaction for 30 minutes under light-proof conditions, turn on a UV light source with a wavelength of 365 nm to irradiate the mixed solution, continue stirring for 20 minutes, after the irradiation is completed, add glycine to terminate the remaining active sites, use a centrifuge to separate and purify, wash with deionized water, and then place in a freeze dryer, set the temperature to minus 50°C and the vacuum degree to 0.1 mbar for sublimation drying, and the drying time is 48 hours to obtain a thickener;

[0040] S1.2. Add thickener, hydroxypropyl guar gum, polyacrylamide, borax, zirconate, sodium hydroxide pH regulator, diethylenetriamine pentaacetic acid antiscalant and sodium lauryl sulfate powder to the dry powder feeding system in sequence, and stir with a stirrer to mix the raw materials evenly;

[0041] S1.3. Use a high-speed agitator with an efficient dispersion system to add water into the mixing tank, and add dry powder into the water through the dry powder feeding system. The addition rate is 1% of the total mass of dry powder per minute, and the stirring rate is 1000rpm, until the polymer is completely dissolved to form a uniform solution to obtain the fracturing fluid.

[0042] Embodiment 3: A method for online fracturing of dry powder polymer for oil and gas fields, comprising the following steps:

[0043] S1.1, weigh the following raw materials in parts by weight: 5 parts by weight of thickener, 23 parts by weight of hydroxypropyl guar gum, 15 parts by weight of polyacrylamide, 6 parts by weight of borax, 3 parts by weight of zirconate, 6 parts by weight of sodium hydroxide pH regulator, 0.5 parts by weight of diethylenetriamine pentaacetic acid antiscalant and 0.7 parts by weight of sodium lauryl sulfate;

[0044] The thickener is prepared by mixing polyethyleneimine and 6-[(4-azido-2-nitrophenyl)amino]hexanoic acid sulfonyl succinimide ester in a mass ratio of 1:0.1; the mass ratio of oleic acid to polyethyleneimine is 0.01:1; the molar ratio of glycine to 6-[(4-azido-2-nitrophenyl)amino]hexanoic acid sulfonyl succinimide ester is 1.5:1;

[0045] Use a metering pump to add polyethyleneimine with a molecular weight of 750 kDa to water at 25°C, the mass fraction of the polyethyleneimine solution is 1%, turn on a high shear mixer to stir thoroughly until it is completely dissolved, then add oleic acid with a mass fraction of 1%, continue stirring until it is completely evenly distributed, then add 6-[(4-azido-2-nitrophenyl)amino]hexanoic acid sulfonic acid succinimide ester to the solution containing polyethyleneimine and oleic acid, adjust the pH of the mixed solution to 8 with a mass fraction of 3% sodium hydroxide solution, stir the reaction for 30 minutes under light-proof conditions, turn on a UV light source with a wavelength of 365 nm to irradiate the mixed solution, continue stirring for 20 minutes, after the irradiation is completed, add glycine to terminate the remaining active sites, use a centrifuge to separate and purify, wash with deionized water, and then place in a freeze dryer, set the temperature to minus 50°C and the vacuum degree to 0.1 mbar for sublimation drying, and the drying time is 48 hours to obtain a thickener;

[0046] S1.2. Add thickener, hydroxypropyl guar gum, polyacrylamide, borax, zirconate, sodium hydroxide pH regulator, diethylenetriamine pentaacetic acid antiscalant and sodium lauryl sulfate powder to the dry powder feeding system in sequence, and stir with a stirrer to mix the raw materials evenly;

[0047] S1.3. Use a high-speed agitator with an efficient dispersion system to add water into the mixing tank, and add dry powder into the water through the dry powder feeding system. The addition rate is 1% of the total mass of dry powder per minute, and the stirring rate is 1000rpm, until the polymer is completely dissolved to form a uniform solution to obtain the fracturing fluid.

[0048] Embodiment 4: A method for online fracturing of dry powder polymer for oil and gas fields, comprising the following steps:

[0049] S1.1, weigh the following raw materials in parts by weight: 5 parts by weight of thickener, 18 parts by weight of hydroxypropyl guar gum, 11 parts by weight of polyacrylamide, 2 parts by weight of borax, 1 part by weight of zirconate, 3 parts by weight of sodium hydroxide pH regulator, 0.1 parts by weight of diethylenetriamine pentaacetic acid antiscalant and 0.5 parts by weight of sodium lauryl sulfate;

[0050] The thickener is prepared by mixing polyethyleneimine and 6-[(4-azido-2-nitrophenyl)amino]hexanoic acid sulfonyl succinimide ester in a mass ratio of 1:0.08; the mass ratio of oleic acid to polyethyleneimine is 0.001:1; the molar ratio of glycine to 6-[(4-azido-2-nitrophenyl)amino]hexanoic acid sulfonyl succinimide ester is 1.2:1;

[0051] Use a metering pump to add polyethyleneimine with a molecular weight of 750 kDa to water at 25°C, the mass fraction of the polyethyleneimine solution is 1%, turn on a high shear mixer to stir thoroughly until it is completely dissolved, then add oleic acid with a mass fraction of 1%, continue stirring until it is completely evenly distributed, then add 6-[(4-azido-2-nitrophenyl)amino]hexanoic acid sulfonic acid succinimide ester to the solution containing polyethyleneimine and oleic acid, adjust the pH of the mixed solution to 8 with a mass fraction of 3% sodium hydroxide solution, stir the reaction for 30 minutes under light-proof conditions, turn on a UV light source with a wavelength of 365 nm to irradiate the mixed solution, continue stirring for 20 minutes, after the irradiation is completed, add glycine to terminate the remaining active sites, use a centrifuge to separate and purify, wash with deionized water, and then place in a freeze dryer, set the temperature to minus 50°C and the vacuum degree to 0.1 mbar for sublimation drying, and the drying time is 48 hours to obtain a thickener;

[0052] S1.2. Add thickener, hydroxypropyl guar gum, polyacrylamide, borax, zirconate, sodium hydroxide pH regulator, diethylenetriamine pentaacetic acid antiscalant and sodium lauryl sulfate powder to the dry powder feeding system in sequence, and stir with a stirrer to mix the raw materials evenly;

[0053] S1.3. Use a high-speed agitator with an efficient dispersion system to add water into the mixing tank, and add dry powder into the water through the dry powder feeding system. The addition rate is 1% of the total mass of dry powder per minute, and the stirring rate is 1000rpm, until the polymer is completely dissolved to form a uniform solution to obtain the fracturing fluid.

[0054] Embodiment 5: A method for online fracturing of dry powder polymer for oil and gas fields, comprising the following steps:

[0055] S1.1, weigh the following raw materials in parts by weight: 1 part by weight of thickener, 23 parts by weight of hydroxypropyl guar gum, 15 parts by weight of polyacrylamide, 6 parts by weight of borax, 3 parts by weight of zirconate, 6 parts by weight of sodium hydroxide pH regulator, 0.5 parts by weight of diethylenetriamine pentaacetic acid antiscalant and 0.7 parts by weight of sodium lauryl sulfate;

[0056] The thickener is prepared by mixing polyethyleneimine and 6-[(4-azido-2-nitrophenyl)amino]hexanoic acid sulfonyl succinimide ester in a mass ratio of 1:0.08; the mass ratio of oleic acid to polyethyleneimine is 0.01:1; the molar ratio of glycine to 6-[(4-azido-2-nitrophenyl)amino]hexanoic acid sulfonyl succinimide ester is 1.5:1;

[0057] Use a metering pump to add polyethyleneimine with a molecular weight of 750 kDa to water at 25°C, the mass fraction of the polyethyleneimine solution is 1%, turn on a high shear mixer to stir thoroughly until it is completely dissolved, then add oleic acid with a mass fraction of 1%, continue stirring until it is completely evenly distributed, then add 6-[(4-azido-2-nitrophenyl)amino]hexanoic acid sulfonic acid succinimide ester to the solution containing polyethyleneimine and oleic acid, adjust the pH of the mixed solution to 8 with a mass fraction of 3% sodium hydroxide solution, stir the reaction for 30 minutes under light-proof conditions, turn on a UV light source with a wavelength of 365 nm to irradiate the mixed solution, continue stirring for 20 minutes, after the irradiation is completed, add glycine to terminate the remaining active sites, use a centrifuge to separate and purify, wash with deionized water, and then place in a freeze dryer, set the temperature to minus 50°C and the vacuum degree to 0.1 mbar for sublimation drying, and the drying time is 48 hours to obtain a thickener;

[0058] S1.2. Add thickener, hydroxypropyl guar gum, polyacrylamide, borax, zirconate, sodium hydroxide pH regulator, diethylenetriamine pentaacetic acid antiscalant and sodium lauryl sulfate powder to the dry powder feeding system in sequence, and stir with a stirrer to mix the raw materials evenly;

[0059] S1.3. Use a high-speed agitator with an efficient dispersion system to add water into the mixing tank, and add dry powder into the water through the dry powder feeding system. The addition rate is 1% of the total mass of dry powder per minute, and the stirring rate is 1000rpm, until the polymer is completely dissolved to form a uniform solution to obtain the fracturing fluid.

[0060] Embodiment 6: A method for online fracturing of dry powder polymer for oil and gas fields, comprising the following steps:

[0061] S1.1, weigh the following raw materials in parts by weight: 10 parts by weight of thickener, 23 parts by weight of hydroxypropyl guar gum, 15 parts by weight of polyacrylamide, 6 parts by weight of borax, 3 parts by weight of zirconate, 6 parts by weight of sodium hydroxide pH regulator, 0.5 parts by weight of diethylenetriamine pentaacetic acid antiscalant and 0.7 parts by weight of sodium lauryl sulfate;

[0062] The thickener is prepared by mixing polyethyleneimine and 6-[(4-azido-2-nitrophenyl)amino]hexanoic acid sulfonyl succinimide ester in a mass ratio of 1:0.08; the mass ratio of oleic acid to polyethyleneimine is 0.01:1; the molar ratio of glycine to 6-[(4-azido-2-nitrophenyl)amino]hexanoic acid sulfonyl succinimide ester is 1.5:1;

[0063] Use a metering pump to add polyethyleneimine with a molecular weight of 750 kDa to water at 25°C, the mass fraction of the polyethyleneimine solution is 1%, turn on a high shear mixer to stir thoroughly until it is completely dissolved, then add oleic acid with a mass fraction of 1%, continue stirring until it is completely evenly distributed, then add 6-[(4-azido-2-nitrophenyl)amino]hexanoic acid sulfonic acid succinimide ester to the solution containing polyethyleneimine and oleic acid, adjust the pH of the mixed solution to 8 with a mass fraction of 3% sodium hydroxide solution, stir the reaction for 30 minutes under light-proof conditions, turn on a UV light source with a wavelength of 365 nm to irradiate the mixed solution, continue stirring for 20 minutes, after the irradiation is completed, add glycine to terminate the remaining active sites, use a centrifuge to separate and purify, wash with deionized water, and then place in a freeze dryer, set the temperature to minus 50°C and the vacuum degree to 0.1 mbar for sublimation drying, and the drying time is 48 hours to obtain a thickener;

[0064] S1.2. Add thickener, hydroxypropyl guar gum, polyacrylamide, borax, zirconate, sodium hydroxide pH regulator, diethylenetriamine pentaacetic acid antiscalant and sodium lauryl sulfate powder to the dry powder feeding system in sequence, and stir with a stirrer to mix the raw materials evenly;

[0065] S1.3. Use a high-speed agitator with an efficient dispersion system to add water into the mixing tank, and add dry powder into the water through the dry powder feeding system. The addition rate is 1% of the total mass of dry powder per minute, and the stirring rate is 1000rpm, until the polymer is completely dissolved to form a uniform solution to obtain the fracturing fluid.

[0066] Comparative Example 1: The method of Example 2 was adopted without adding a thickener.

[0067] Comparative Example 2: The method of Example 2 was adopted, and the thickener contained only polyethyleneimine, and was not modified with 6-[(4-azido-2-nitrophenyl)amino]hexanoic acid sulfonic acid succinimide ester.

[0068] Comparative Example 3: The method of Example 2 was adopted, and the thickener contained only 6-[(4-azido-2-nitrophenyl)amino]hexanoic acid sulfonic acid succinimide ester, and was not modified with polyethyleneimine.

[0069] The present invention adopts a dry powder polymer online mixing fracturing method for oil and gas fields prepared by using a thickener, wherein the performance index inspection items and inspection standards of the dry powder polymer online mixing fracturing method for oil and gas fields are as follows:

[0070] According to the SY / T 376-2008 "General Technical Conditions for Fracturing Fluids" standard, the apparent viscosity of the base fluid and the temperature and shear resistance of the dry powder polymer were tested. Water was added to the dry powder polymer and stirred to mix evenly. The mixture was placed in a constant temperature water bath at 30°C for 4 hours. The rotation speed was 100 r / min (shear rate was 170s -1 ) and then set the pressure of the autoclave to 10 MPa and the temperature to 100 °C. Keep the sample under the set conditions for 24 hours and use a rotational viscometer at 170 s -1 At the shear rate, the apparent viscosity of the base fluid was tested again, and the apparent viscosity change rate of the base fluid under high temperature and high pressure was calculated. The viscosity change rate = (initial base fluid apparent viscosity - apparent viscosity of the base fluid under high temperature and high pressure) / initial base fluid apparent viscosity × 100%. The temperature and shear resistance was tested at 120°C, 170s -1 The test was carried out for 120 min under the given conditions.

[0071] According to the above standards, the online mixing fracturing method of dry powder polymer for oil and gas fields prepared in the above Examples 1-6 and Comparative Examples 1-3 was tested, and the obtained data are shown in Table 1:

[0072] Table 1 Performance data of Examples 1-6 and Comparative Examples 1-3

[0073]

[0074] The above data fully show that compared with Comparative Examples 1-3, Examples 1-6 can fully show the effect of the thickener on the stability of the dry powder polymer for oil and gas fields.

[0075] Since the present invention adopts a thickener to prepare a dry powder polymer for oil and gas fields, the stability of the dry powder polymer for oil and gas fields is effectively improved by the thickener, as follows:

[0076] It can be seen from Examples 1-3 that as the proportion of the thickener component continues to increase, the stability of the dry powder polymer for oil and gas fields first increases and then decreases. This is because as the content of 6-[(4-azido-2-nitrophenyl)amino]hexanoic acid sulfonic acid succinimide ester in the thickener increases, the amount of the cross-linking agent gradually increases, and the number of cross-linking points in the polymer network increases, which increases the rigidity and stability of the network, thereby improving the overall stability and viscosity. When the amount of the cross-linking agent is too much, the cross-linking points are too dense, which will cause the network to become rigid, or even "over-cross-linking" will occur, which will cause the stress inside the network to concentrate, making it easy to break or degrade, thereby reducing the stability.

[0077] It can be seen from Examples 2 and 4 that as the content of other components in the dry powder polymer for oil and gas fields continues to change, the stability of the dry powder polymer for oil and gas fields does not change significantly. This is because small changes in these components within a certain range will not significantly affect the stability of the final polymer. Therefore, the stability of the dry powder polymer for oil and gas fields changes little.

[0078] It can be seen from Examples 2, 5 and 6 that the stability of the dry powder polymer for oil and gas fields changes continuously with the continuous change of the thickener content. This is because an appropriate amount of cross-linking can effectively enhance the connection between polymer molecules, making the network structure stronger, thereby improving the stability and mechanical strength of the network. When the thickener content continues to increase, the cross-linking points become too dense, causing the polymer to become too viscous, the fluidity decreases significantly, and the cross-linked network structure becomes hard and brittle, thereby reducing the overall stability.

[0079] According to the above test experiments, the online mixing fracturing method of dry powder polymer for oil and gas fields prepared according to Example 2 has the best performance, so Example 2 is taken as the best example;

[0080] By comparing Example 2 with Comparative Examples 1-3, it can be seen that:

[0081] In Comparative Example 1, no thickener was added, and the stability of the dry powder polymer for oil and gas fields was poor. This is because an important function of the thickener is to form a stable three-dimensional network structure through a cross-linking reaction, thereby enhancing the degree of cross-linking of the polymer, thereby further improving the stability of the polymer. When no thickener is added, the stability of the polymer in a complex environment is poor, and it is easy to degrade under high temperature or high pressure, resulting in structural damage and performance degradation.

[0082] In Comparative Example 2, the thickener contains only polyethyleneimine, and is not modified with 6-[(4-azido-2-nitrophenyl)amino]hexanoic acid sulfonic acid succinimide ester. The stability of the dry powder polymer for oil and gas fields is poor. This is because Sulfo-SANPAH, as a highly efficient cross-linking agent, can undergo a cross-linking reaction with the amine groups in PEI to form a denser and more stable cross-linked network, which makes it have better stability in harsh environments. However, the lack of Sulfo-SANPAH will lead to insufficient cross-linking density, which is easy to deform or break under the action of external force, and thus the stability is deteriorated.

[0083] The thickener in Comparative Example 3 contains only 6-[(4-azido-2-nitrophenyl)amino]hexanoic acid sulfonic acid succinimide ester, and is not modified with polyethyleneimine. The stability of the dry powder polymer for oil and gas fields is poor. This is because Sulfo-SANPAH itself is a cross-linking agent, which needs to undergo a cross-linking reaction with the polymer PEI containing active groups to form a stable cross-linked network. Without PEI as a cross-linking matrix, Sulfo-SANPAH cannot independently form a stable three-dimensional network structure, nor can it effectively participate in the cross-linking reaction of the polymer, and cannot be used as a thickener to adjust the viscosity of the polymer. Therefore, the stability of the polymer is poor.

[0084] In summary, the thickener was prepared by modifying 6-[(4-azido-2-nitrophenyl)amino]hexanoic acid sulfonic acid succinimide ester with polyethyleneimine. The double cross-linking mechanism was used to further improve the degree of cross-linking, thereby improving the viscosity and stability of the polymer, thereby improving the sand carrying capacity and suspension capacity of the polymer, ensuring the structural integrity of the fracturing fluid under high temperature and high pressure environments, and thus broadening the applicability of the fracturing fluid.

[0085] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited by the above embodiments, and the above embodiments and descriptions are only preferred examples of the present invention, and are not intended to limit the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of the present invention to be protected.

Claims

1. An online fracturing method for dry powder polymers for oil and gas fields, characterized in that: S1.1, weigh the following raw materials in parts by weight: 1-10 parts by weight of thickener, 18-23 parts by weight of hydroxypropyl guar gum, 11-15 parts by weight of polyacrylamide, 2-6 parts by weight of borax, 1-3 parts by weight of zirconate, 3-6 parts by weight of sodium hydroxide pH regulator, 0.1-0.5 parts by weight of diethylenetriamine pentaacetic acid antiscalant and 0.5-0.7 parts by weight of sodium lauryl sulfate; The thickener is prepared by mixing polyethyleneimine and 6-[(4-azido-2-nitrophenyl)amino]hexanoic acid sulfonic acid succinimide ester in a mass ratio of 1:0.05-0.1; S1.

2. Add thickener, hydroxypropyl guar gum, polyacrylamide, borax, zirconate, sodium hydroxide pH regulator, diethylenetriamine pentaacetic acid antiscalant and sodium lauryl sulfate powder to the dry powder feeding system in sequence, and stir with a stirrer to mix the raw materials evenly; S1.

3. Use a high-speed agitator with an efficient dispersion system to add water into a mixing tank, and add the dry powder into the water through the dry powder feeding system at a stirring rate of 600-1000 rpm until the polymer is completely dissolved to form a uniform solution to obtain a fracturing fluid; In S1.3, the addition rate of the dry powder feeding system is 0.5-1% of the total mass of dry powder added per minute; The steps of preparing the thickener are specifically as follows: Use a metering pump to add polyethyleneimine to water at 25-35°C, turn on a high shear mixer to stir thoroughly until it is completely dissolved, then add oleic acid, continue stirring until it is completely evenly distributed, then add 6-[(4-azido-2-nitrophenyl)amino]hexanoic acid sulfonic acid succinimide ester to the solution containing polyethyleneimine and oleic acid, adjust the pH of the mixed solution to 7-8 with a sodium hydroxide solution, stir the reaction for 30-40 minutes under light-proof conditions, turn on a UV light source to irradiate the mixed solution, and continue stirring for 10-20 minutes. After the irradiation is completed, add glycine to terminate the remaining active sites, use a centrifuge to separate and purify, wash with deionized water, and then place in a freeze dryer, set the temperature to minus 30-50°C and the vacuum degree to 0.1-0.3mbar for sublimation drying, and the drying time is 12-48h to obtain a thickener.

2. The on-line mixing and fracturing method of dry powder polymer for oil and gas fields according to claim 1, characterized in that: The molecular weight of the polyethyleneimine is 500-750 kDa.

3. The on-line mixing and fracturing method of dry powder polymer for oil and gas fields according to claim 1, characterized in that: The mass fraction of the polyethyleneimine solution is 1-3%.

4. The on-line mixing and fracturing method of dry powder polymer for oil and gas fields according to claim 1, characterized in that: The mass fraction of the oleic acid is 1-10%.

5. The on-line mixing and fracturing method of dry powder polymer for oil and gas fields according to claim 1, characterized in that: The mass ratio of the oleic acid to the polyethyleneimine is 0.001-0.01:

1.

6. The on-line mixing and fracturing method of dry powder polymer for oil and gas fields according to claim 1, characterized in that: The mass fraction of the sodium hydroxide solution is 1-5%.

7. The on-line fracturing method for dry powder polymer for oil and gas fields according to claim 1, characterized in that: The wavelength range of the UV light source is 320-365 nm.

8. The on-line mixing and fracturing method of dry powder polymer for oil and gas fields according to claim 1, characterized in that: The molar ratio of glycine to 6-[(4-azido-2-nitrophenyl)amino]hexanoic acid sulfonic acid succinimide ester is 1.2-1.5:1.

Citation Information

Patent Citations

  • Environment-friendly waterproof sealant and preparation method thereof

    CN103013399A

  • Cellulose blended modified polyvinyl alcohol fracturing fluid and preparation method thereof

    CN104974739A